THE USE OF SERIES IMAGE MEDIA TO IMPROVE CIVICS LEARNING OUTCOMES OF STUDENTS WITH INTELLECTUAL DISABILITYIN - Nisa’ul Kasanah; Tomas Iriyanto (Department of Special Education, 2016)
Civics learning is one of the subjects related with daily activities. The purpose of this research is to determain the using of series image media to incrase of outcomes learning the civics subject on schools discipline materials and to determine the increase of outcomes learning the civics subject on schools discipline materials in school to the students with intellectual disability in grade II after given learning with series image media.The approach in this research is a classroom action research (CAR). The conclusion of the study is the use of the series image media in the schools discipline material can improve student learning outcomes. The indicators was the incrased values of the average student and the percentage of successful students from pre action, one cycle to the next cycle, in pre action was 48,75, the first cycle was 56,25 and the second cycle was 86,25.